The Relationship between Pedagogical Competence of Physical Education Teachers and Student Learning Motivation in Pademawu 2 Public Middle School, Pamekasan Regency - Dwi Septiawan Azista; Noer Wachid Riqza Firdaus; Rendra Kusuma; Mohammad Hasan Basri (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Physical Education, Sports, and Health (PJOK) requires teachers to combine instructional competence, effective communication, assessment, and appropriate learning media to maintain students’ engagement. This study examined the relationship between students’ perceptions of PJOK teachers’ pedagogical competence and their learning motivation at SMP Negeri 2 Pademawu, Pamekasan Regency. A quantitative correlational design was applied to 157 students from Grades VII–IX selected through proportionate stratified random sampling from a population of 257 students. Data were collected using two four-point Likert-scale questionnaires comprising 35 items on pedagogical competence and 24 items on learning motivation. The instruments were validated through expert judgment and pilot testing, with all items meeting the validity criterion and Cronbach’s alpha coefficients of 0.941 and 0.909, respectively. Descriptive statistics, Shapiro–Wilk normality testing, ANOVA-based linearity testing, and Pearson Product-Moment correlation were employed for data analysis. The findings showed that pedagogical competence and learning motivation were both at high levels, with achievement scores of 77.91% and 78.56%, respectively. Effective communication was the strongest pedagogical dimension, whereas ICT utilization showed the lowest achievement. Pearson analysis revealed a positive and significant relationship between pedagogical competence and learning motivation (r = 0.614, p < 0.001), with an associated contribution of 37.73%. The findings highlight the importance of strengthening teachers’ pedagogical practices, particularly communication and technology-supported instruction, to foster more motivating PJOK learning environments.